Pureed Foods: Texture Testing with the Slump Test - Wendy J. Dahl (EDIS)
For individuals with dysphagia, the texture of puréed foods is extremely important. If the puréed foods are either too thick or too thin, it can make it more difficult to swallow. The slump test is a quick, easy, and inexpensive way to assess the texture of foods. This 4-page fact sheet describes the slump test, how to perform a slump test, and how the slump test can be used to evaluate the texture of puréed foods. Written by Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, December 2015.